Урожайный огород на 6 сотках - Кизима Галина Александровна (Серия "Мир сада и огорода", 2023)
Экземпляры: ЦБ (20230508) / Инвентарный номер: 60816 / Цена: 291.39 / Сис.шифр: 42.34 / Авт.знак: К 38 / ГРНТИ: 68.35.51 / ББК: 42.34